TiO2 ALD Coating of Amorphous TiO2 Nanotube Layers: Inhibition of the Structural and Morphological Changes Due to Water Annealing - Ng, Siowwoon; Sopha, Hanna; Zazpe, Raul; Spotz, Zdenek; Bijalwan, Vijay; Dvorak, Filip; Hromadko, Ludek; Prikryl, Jan; Macak, Jan M. (Frontiers in Chemistry, 2019)
The present work presents a strategy to stabilize amorphous anodic self-organized TiO2 nanotube layers against morphological changes and crystallization upon extensive water soaking. The growth of needle-like nanoparticles was observed on the outer and inner walls of amorphous nanotube layers after extensive water soakings, in line with the literature on water annealing. In contrary, when TiO2 nanotube layers uniformly coated by thin TiO2 using atomic layer deposition (ALD) were soaked in water, the growth rates of needle-like nanoparticles were substantially reduced. We investigated the soaking effects of ALD TiO2 coatings with different thicknesses and deposition temperatures. Sufficiently thick TiO2 coatings (≈8.4 nm) deposited at different ALD process temperatures efficiently hamper the reactions between water and F- ions, maintain the amorphous state and preserve the original tubular morphology. This work demonstrates the possibility of having a robust amorphous 1D TiO2 nanotube layers that are very stable in water. This is very practical for diverse bio-medical applications that are accompanied by extensive contact with an aqueous environment.